Development of a Didactic Sequence to guide technicians in the educational conduct of school visits to sewage treatment plants (Research, Society and Development, 2021)
The present work consists of the development of a didactic sequence (DS) to guide technical professionals in conducting visits to Wastewater Treatment Plants (WWTP). The didactic sequence was worked as a strategy to enhance the visit by transforming the technical knowledge into taught knowledge, and its development was articulated with the theoretical content taught in public elementary and high schools. To analyze the chemistry content, two books used in public schools in the city of Itajubá-MG were chosen. Each step of sewage treatment represents an element in the DS, which was elaborated based on the theory of didactic transposition advocated by Chevallard (1991) and elaborated considering the steps of the DS advocated by Zabala (1998). The DS was analyzed according to the principles of Didactic Transposition (DT) advocated by Astolfi (1995). It was also proposed the use of a questionnaire to be filled in by the visitor at the end of the visit in order to improve the DS. It is hoped that this DS will help the technical professionals during the visit and to provide a better use of the visit by students of basic education.